Bacillus thuringiensis characterization: Morphology, physiology, biochemistry, pathotype, cellular, and molecular aspects - Rabinovitch, Leon; Vivoni, Adriana Marcos; Machado, Vilmar; Knaak, Neiva; Berlitz, Diouneia Lisiane; Polanczyk, Ricardo Antonio [UNESP]; Fiuza, Lidia Mariana (Springer Nature, 2017)
In this publication, Bacillus thuringiensis and Lysinibacillus sphaericus - characterization and use in the field of biocontrol, this chapter can be seen as a brief general and historical introduction to the central theme of the book, where data on the cellular physiology, biochemical, genetic, molecular, and toxicological aspects of the bacterium, B. Thuringiensis (Bt), are reported. This predominant entomopathogenic prokaryote was discovered and denominated Bt around a century ago, between 1902 and 1911. From the microbiological point of view, this bacterium is ubiquitous, Gram-positive, produces ellipsoidal but predominantely cilindrical endospores (central to paracentral) and contains a parasporal inclusion body called crystal or 8-endotoxin. The crystal is constituted of Cry proteins with molecular weight between 30 kDa and 140 kDa, which are coded by cry genes. On the other hand, this bacterial species synthesizes several enzymes and toxins that give them a wide adaptation to natural habitats. Bt strains have been studied and, over time, characterized and described as toxic and specific for Lepidoptera, Diptera, Coleoptera, Nematoda, Protozoa, Trematoda, Acari, Hymenoptera, Hemiptera, Orthoptera, Isoptera, Mallophaga, and among other target pests. Globally, 82 Bt serovars sometimes called subspecies were described until 1999, which currently correspond to more than 700 cry genes distributed in about 70 classes. The nomenclature review of cry genes, which encode Bt Cry proteins, has been published by Crickmore et al. And has been constantly updated on the website: Http://www.lifesci.sussex.ac.uk/home/Neil_Crickmore/Bt/.
Keywords: B. Thuringiensis; Bacillus spp.; Bacteria; Biochemistry; DNA; Genetics; Physiology; Toxicology